Rightsizing the government: the indian experience - Jha, Nikhilesh (2002)
The concept of rightsize in government is yet to firm up. This can be appreciated by considering the wide variance in the number of public employees as a percentage of population in a few countries. As of 1991, there were 120 public employees for every 1000 members of population in France, compared to 81 in the United States, 80 in the United Kingdom and 40 in Japan.' In case of India, the figure was 21.7 for a population of 1000 in 1994. The interesting fact is that all these countries have been talking of, rightsizing the government and have made serious efforts for this. The statistics and the perception of different countries show that the rightsizing issue does not have to do anything with the size of the public service. - Reproduced.
Keywords: Civil service - India; Civil service